Ocean acidification and marine wildlife : physiological and behavioral impacts - Liu, Guangxu (Academic Press, 2021)
"Ocean Acidification and Marine Wildlife: Physiological and Behavioral Impacts provides comprehensive knowledge on how decreases in the pH of the world's oceans is affecting marine organisms. The book synthesizes recent findings about the impacts of ocean acidification (OA) on marine animals, covering the physiological and behavioral effects upon marine invertebrates and vertebrates, the potential physiological and molecular mechanism affects, and interactions of OA with other environmental factors. Written by international experts in this research field, this book summarizes new discoveries of OA effects on fertilization, embryonic development, biomineralization, metabolism, immune response, foraging, anti-predation, habitat selection, and the social hierarchy of marine animals. This is an important resource for researchers and practitioners in marine conservation, marine wildlife studies, and climate change studies. In addition, it will serve as a valuable text for marine biology and animal science students. Key Features: Examines the impacts of carbon dioxide increases in the world's oceans relating to marine vertebrates and invertebrates; Identifies environmental factors, including climate change and pollution and how they increase the negative effects of ocean acidification; Facilitates a better understanding of ocean acidification effects for conservationism and future prevention."--Publisher's description